2019
DOI: 10.1002/jcb.28687
|View full text |Cite
|
Sign up to set email alerts
|

An immunosuppressive peptide from the horsefly inhibits inflammation by repressing macrophage maturation and phagocytosis

Abstract: Ectoparasites repress host immune responses while they obtain nutrition from their hosts. Understanding the immunosuppressive mechanisms between ectoparasites and their hosts will provide new strategies to develop potential immunosuppressive drugs against immune disorder diseases. Previously, we have discovered that a small peptide, immunoregulin HA, from the horsefly (Hybomitra atriperoides) may play an immunosuppressive role in rat splenocytes. However, the targeting cells and detailed mechanisms of immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It was found that cecropin-TY1, immunomodulatory protein HA and immunoregulin TPs in Tabanus SGE had strong immune and anti-inflammatory effects [2,6,7] . Immunomodulatory protein HA inhibits the maturation and phagocytosis of macrophages [6] . Tabimmunregulins increased the production of IL-10 and decreased IFN-γ secretion [2] .…”
Section: Pharmacological Action Of Tabanusmentioning
confidence: 99%
“…It was found that cecropin-TY1, immunomodulatory protein HA and immunoregulin TPs in Tabanus SGE had strong immune and anti-inflammatory effects [2,6,7] . Immunomodulatory protein HA inhibits the maturation and phagocytosis of macrophages [6] . Tabimmunregulins increased the production of IL-10 and decreased IFN-γ secretion [2] .…”
Section: Pharmacological Action Of Tabanusmentioning
confidence: 99%